ILLOCUTIONARY ACTS IN MARNIE’S WORLD MOVIE - Mbejo, Heldansia Y; Sama, Gratiana; Kara, Yuliana M D K; Ita, Efrida (Fakultas Hukum dan Sosial Humaniora Universitas Flores, 2024)
The purpose of this study is to find out the types and the functions of illocutionary acts in Marnie’s World movie. The study used theory based on Austin to classify the types of illocutionary acts, and functions of illocutionary acts based on Leech. This study used the descriptive qualitative method. In process of collecting data, the writer used several steps, as follows; firstly, watched Marnie’s World movie continuously. Secondly, wrote all utterances from Marnie’s World movie, then classified the utterance into types and functions of illocutionary acts. The results of this study showed that there are 25 utterances in which containing the 5 types and 4 functions of illocutionary acts. The types of illocutionary acts in which found in Marnie’s World movie as follows; verdictive, exercitive, commisive, behabitive, and expositive. Meanwhile, the functions are competitive, convivial, collaborative, and conflictive.